2020
DOI: 10.1007/978-3-030-53956-6_27
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive Bacterial Foraging Optimization Based on Roulette Strategy

Abstract: Bacterial foraging optimization has drawn great attention and has been applied widely in various fields. However, BFO performs poorly in convergence when coping with more complex optimization problems, especially multimodal and high dimensional tasks. Aiming to address these issues, we therefore seek to propose a hybrid strategy to improve the BFO algorithm in each stage of the bacteria’s’ foraging behavior. Firstly, a non-linear descending strategy of step size is adopted in the process of flipping, where a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To solve this problem, the optimal individual position is perturbed in each iteration, and only one individual is randomly mutated in each iteration. That is, when the sparrow finds the optimal solution, the enhanced Tent chaos is used to mutate the optimal sparrow individual, which further improves the global convergence accuracy and optimizes the shortcomings of the original algorithm in global search and local search [78]. Therefore, in TFSSA, the optimal sparrow individuals are changed by Equations ( 17) and (18).…”
Section: Optimal Individual Mutation By ψ-Tent Chaosmentioning
confidence: 99%
“…To solve this problem, the optimal individual position is perturbed in each iteration, and only one individual is randomly mutated in each iteration. That is, when the sparrow finds the optimal solution, the enhanced Tent chaos is used to mutate the optimal sparrow individual, which further improves the global convergence accuracy and optimizes the shortcomings of the original algorithm in global search and local search [78]. Therefore, in TFSSA, the optimal sparrow individuals are changed by Equations ( 17) and (18).…”
Section: Optimal Individual Mutation By ψ-Tent Chaosmentioning
confidence: 99%
“…The algorithm is aligned with three fundamental processes, primarily elimination-dispersal, reproduction, and chemotaxis [163]. The utility of BFOA in agricultural image processing could be inferred from published research, which suggested that BFOA could complement other algorithms in farms, including GA and ACOA; this is because the algorithm has been proven extremely effective in enhancing machine learning capabilities, agricultural machine/vehicle routing, image processing, dynamic environment optimization, and PID controller design [164]. The potential applications can be enhanced under a hyper-algorithm scenario where BFOA is paired with other swarm intelligence algorithms.…”
Section: Bacterial Foraging Optimization Algorithms (Bfoa)mentioning
confidence: 99%